Dynameric Collagen Self‐Healing Membranes with High Mechanical Strength for Effective Cell Growth Applications. Issue 71 (16th November 2020) - Zhang, Yan; Zhang, Ye; Cui, Han; Barboiu, Mihail; Chen, Jinghua
Abstract: The fabrication of biocompatible adaptive materials with high stiffness and self‐healing properties for medical applications is a challenging endeavor. Collagen is a major extracellular matrix component acting as a substrate for cell adhesion and migration. Dynamers are constitutional polymers whose monomeric components are linked through reversible bonds, able to modify their constitution through reversible exchange of their components. In the current work, we demonstrate that the rational combination of collagen and dynameric networks connected with reversible covalent imine bonds is a very important and previously unreported strategy to provide biocompatible membranes with self‐healing ability and excellent mechanical strength. The key challenge in the construction of such membranes is the required adaptive interaction between collagen chains and the dynamic cross‐linkers, preventing the formation of defects. For example, by varying structure and molecular lengths of the dynamers, the tensile strength of the dynameric membranes reach over 80 MPa, more than 400 % higher than that observed for the reference collagen membrane, and the highest value for break strain found, was 19 %. The self‐healing properties were observed when reconnecting two membrane pieces or even from crushed status of the membranes. Moreover, both MTT assay and confocal laser scanning microscopy method demonstrated the good biocompatibility of the collagen membranes, leaving more than 90 % viability for NIH 3T3 cells after 24 h co‐culture. Abstract : Self‐healing technology : Dynameric collagen membranes with high mechanical strength, biocompatibility and self‐healing properties have been prepared, showing a great potential for biomedical applications.